Application of Dynamic 18F-FDG PET/CT for Distinguishing Intrapulmonary Metastases from Synchronous Multiple Primary Lung Cancer - Weize Lv; Min Yang; Hongcheng Zhong; Xiaojin Wang; Shuai Yang; Lei Bi; Jianzhong Xian; Xiaofeng Pei; Xinghua He; Ying Wang; Zhong Lin; Qingdong Cao; et al. (Molecular Imaging)
It has been a big challenge to distinguish synchronous multiple primary lung cancer (sMPLC) from primary lung cancer with intrapulmonary metastases (IPM). We aimed to assess the clinical application of dynamic 18F-FDG PET/CT in patients with multiple lung cancer nodules. We enrolled patients with multiple pulmonary nodules who had undergone dynamic 18F-FDG PET/CT and divided them into sMPLC and IPM groups based on comprehensive features. The SUVmax, fitted Ki value based on dynamic scanning, and corresponding maximum diameter (Dmax) from the two largest tumors were determined in each patient. We determined the absolute between-tumor difference of SUVmax/Dmax and Ki/Dmax (ΔSUVmax/Dmax; ΔKi/Dmax) and assessed the between-group differences. Further, the diagnostic accuracy was evaluated by ROC analysis and the correlation between ΔSUVmax/Dmax and ΔKi/Dmax from all groups was determined. There was no significant difference for ΔSUVmax/Dmax between the IPM and sMPLC groups, while the IPM group had a significantly higher ΔKi/Dmax than the sMPLC group. The AUC of ΔKi/Dmax for differentiating sMPLC from IPM was 0.80 (cut-off value of Ki=0.0059, sensitivity 79%, specificity 75%, p<0.001). There was a good correlation (Pearson r=0.91, 95% CI: 0.79-0.96, p<0.0001) between ΔSUVmax/Dmax and ΔKi/Dmax in the IPM group but not in the sMPLC group (Pearson r=0.45, p>0.05). Dynamic 18F-FDG PET/CT could be a useful tool for distinguishing sMPLC from IPM. Ki calculation based on Patlak graphic analysis could be more sensitive than SUVmax in discriminating IPM from sMPLC in patients with multiple lung cancer nodules.